DEVELOPMENT OF RAPID TECHNIQUE FOR DETERMINATION OF THE TOTAL MINERALIZATION OF NATURAL WATERS - T. A. Kuchmenko (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2016)
A new approach has been proposed for rapid and easy evaluation of a indicator of quality and properties of natural water - soluble salt content (mineralization). The method of quartz crystal microbalance is employed at load of the mass-sensitive resonator electrode (BAW-type) with investigated water. The degree of correlation between the various indicators related to the contents of salts and insoluble compounds and the level of mineralization obtained by the standard method (gravimetry) has been studied. A procedure for salt weighing by single sensor at unilateral load with small sample of natural water has been developed. The optimal conditions for measurement is established using the design of experiment by model 23 . The possibilities of quartz crystal microbalance for determination of non-volatile compounds in the water are described. The calibration of piezosensor is produced by standard solution NaCl (c = 1.000 g / dm3) at optimal conditions of experiment. The adequacy and accuracy of proposed technique is assessed by the correlation between the results of quartz crystal microbalance and conductometry. The correlation between indicators of mineralization established by quartz crystal microbalance and gravimetry is found. It has been obtained an equation that can be used to calculate the standard indicator of the mineralization by the results of a quartz crystal microbalance using single sensor. The approaches to enhance the analytical capabilities of the developed technique for water with low and high mineralization are proposed. The metrological characteristics of quartz crystal microbalance of insoluble compounds in natural water are estimated. A new technique of determination of the mass concentration of the dry residue in water with a conductivity of 0.2 mS or above has been developed, which can be used for rapid analysis of the water at nonlaboratory conditions and in the laboratory for rapid obtaining the information about a sample.